Degradation of Mangrove Ecosystems in Banyuasin Regency, South Sumatra: Extent of Damage, Causes, and Ecological Impacts - Ali Mahmudi; Bakri; Rozirwan; Ridhah Taqwa (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aims to examine the scale of damage, identify the contributing factors, and analyze the resulting ecological impacts. The research employed a qualitative descriptive approach through field observations, interviews with coastal communities, and a literature review. Observations were conducted to assess the biophysical condition of mangroves, including vegetation density, stand structure, species composition, and indicators of degradation. Interviews were used to gather information on mangrove utilization activities, socio-economic pressures, and community perceptions of environmental change. The literature review supported the interpretation of field findings within the context of regional and global mangrove dynamics. The results indicate that mangrove degradation in Banyuasin is driven by a complex interaction between anthropogenic factors—particularly land conversion, resource exploitation, and coastal development—and natural factors such as abrasion, sedimentation, and tidal flooding. The identified ecological impacts include a decline in coastal protection functions, reduced habitat quality for coastal biota, and decreased carbon storage capacity. The conclusion of this study emphasizes the need for an integrated coastal management strategy that incorporates ecologically appropriate rehabilitation, strengthened governance, and community participation in order to sustainably enhance the resilience of mangrove ecosystems.